Reconceptualizing Narratology. Arguments for a Functionalist and Constructivist Approach to Narrative (ENTHYMEMA, 2011)
This long conversation with Meir Sternberg focuses on some crucial points in narrative theory. Special attention is given, in the first part, to the historical evolution of narrative studies, as well as to the theoretical differences between different paradigms, form Aristotle, through French structuralism, to the present days; in the second part he centers on the explanation of his constructivist ant anti-mimetic model and on the difference with other approaches to narrative studies. Providing two fundamental arguments against what he calls «objectivist approaches», he demonstrates the validity and the theoretical value of some of his most thought-provoking proposals, such as the Proteus Principle and the universals of narrative. Thanks to its explanatory power the interview constitutes a simple introduction to Sternberg’s functional-rhetorical approach and a glimpse at the editorial policy of the journal «Poetics Today».
Keywords: proteus principle; rhetoric; functionalism; narrative; dynamics of time; suspense; curiosity; surprise